Neutrophil Extracellular Traps in Autoimmunity and Allergy: Immune Complexes at Work - Granger, Vanessa; Peyneau, Marine; Chollet-Martin, Sylvie; de Chaisemartin, Luc (Frontiers in Immunology, 2019)
Neutrophil extracellular traps (NETs) have been initially described as main actors in host defense owing to their ability to immobilize and sometimes kill microorganisms. Subsequent studies have demonstrated their implication in the pathophysiology of various diseases, in particular due to the toxic effects of their main components, histones and proteases, on surrounding tissues. Several distinct pathways in response to various triggers have been described. Among these triggers, IgG immune complexes (IC) play an important role because they can bind to several neutrophil FcgRs and induce NET release. Few in vitro studies have documented the intracellular mechanisms of IC-induced NET release and evidence show that the type of FcgR involved is important. In vivo, animal models and clinical studies have highly suggested the importance of IgG IC-induced NET release during autoimmunity and anaphylaxis. In this review we will focus on two autoimmune diseases in which NETs are undoubtedly major players, systemic lupus erythematosus (SLE) (DNA/anti-DNA IgG IC) and rheumatoid arthritis (RA) (citrullinated proteins/anti-citrullinated proteins IgG IC). Both types of IC activate NET release, inducing autoantigen exposure and breaking of immune tolerance. Anaphylaxis is also an example of disease associated with IC-induced NET release, via allergen/specific IgG IC. This newly described additional pathway of anaphylaxis may improve the diagnosis for the patients, and the deleterious role of NETs in this setting requires further studies, in particular in drug-induced anaphylaxis.